Same as it Ever Was? Stability and Change Over 15 Years in a Rural District in Southeastern Australia. Issue 1 (2nd January 2019) - Toman, Eric; Curtis, Allan Lindsay; Mendham, Emily
Abstract: Using longitudinal survey data, this paper explores stability and change in values, beliefs, attitudes, and knowledge among rural landholders. Existing theories predict varying degrees of stability in these constructs. This paper tests these assumptions through data collected by four cross-sectional surveys of rural landowners (>10 ha), completed in one region between 2002 and 2016. The study area includes a mix of social landscapes but agriculture is the dominant land use. Results reveal significant change in measured constructs over time. Nearly all of the items assessing values changed significantly across the study period (seven of eight held values, ten of eleven assigned values). Most belief items (three of five), half of the attitude items (two of four), and all eleven knowledge items also experienced change. While statistically significant, most of the identified changes were relatively modest in scope. Findings suggest the value of longitudinal research to better understand dynamic psychological and social constructs.